Men Coblong; Voicing the everyday agency of Oka Rusmini - Allen, Pamela (Wacana, Journal of the Humanities of Indonesia, 2023)
Starting out as a column in the Bali Post, Oka Rusmini’s alter ego Men Coblong offers, among other things, a feminist perspective on mothers and women and the social relations and cultural practices that confine them. Men Coblong fearlessly voices her view on religious sensitivities, culture, politics and, especially, everyday life. In Men Coblong, the self-titled collection of her columns, the (re)claiming of power operates on two levels. First, we have the journalist Oka Rusmini using words as power to challenge the injustices and absurdities she witnesses in contemporary Indonesia. Second, Oka’s alter ego Men Coblong engages in acts of everyday agency, using a range of strategies, to assert her power as a woman. This analysis of Men Coblong is informed by notions of power, resistance, and agency as conceived by James Scott, Anthony Giddens, and Laura Ahearn. The power that Oka Rusmini is (re)claiming through Men Coblong is the right to confront, protest, and resist through words. Men Coblong reclaims power not through political activism but through enacting everyday agency.